Tumor-derived extracellular vesicles: key drivers of immunomodulation in breast cancer - Li, Jieming; Yu, Shuo; Rao, Min; Cheng, Bomin (Frontiers in Immunology, 2025)
Breast cancer (BC) remains a significant global health challenge characterized by its heterogeneity and treatment complexities. Extracellular vesicles (EVs) are small membranous particles released by cells, facilitating intercellular communication by transporting bioactive molecules such as proteins, lipids, and nucleic acids. Tumor-derived EVs have emerged as pivotal regulators in the tumor microenvironment (TME) and drivers of BC progression. These EVs carry diverse cargoes of bioactive molecules, influencing critical processes such as immune modulation, angiogenesis, and metastasis. By altering the behaviors of immune cells including macrophages, dendritic cells, and T cells, tumor-derived EVs contribute to immune evasion and tumor growth. Furthermore, Tumor-derived EVs play a role in mediating drug resistance, impacting the effectiveness of therapeutic interventions. Understanding the multifaceted roles of BC tumor-derived EVs is essential for the development of innovative therapeutic strategies. Targeting pathways mediated by EVs holds promise for enhancing the efficacy of cancer treatments and improving patient outcomes. This comprehensive review provides insights into the intricate interactions of tumor-derived EVs in immune modulation and BC progression, highlighting potential therapeutic targets and avenues for novel cancer therapies.